Histomorphological aspects of cadaveric skin and its possible use in forensic genetics. (January 2021) - Bailo, Paolo; Andreola, Salvatore; Collini, Federica; Gentile, Guendalina; Maciocco, Francesca; Piccinini, Andrea; Zoja, Riccardo
The skin is rarely considered as good biological material for successful DNA typing when a corpse is found in a leathery, mummified or partially skeletonised state, as bones and teeth are the gold standard in these cases. This study evaluates the histomorphological aspects of nuclear chromatin (Lillie's staining) in leathery and mummified skin samples as an indicator for possible successful DNA typing. Chromatin was found in samples that underwent mummification or partial skeletonisation but not in samples in a wet type of post-mortem transformation, such as saponification or leathery transformation. As a preliminary result, a positive detection of DNA profiles was only observed in 1-year-old mummified or partially skeletonised samples. These findings suggest that specific areas of skin, even from severely deteriorated cadavers, can show nuclear chromatin and DNA. These preliminary results raise the potential use of skin samples as an alternative source of DNA in highly degraded corpses.